(untitled) (Bangladesh Journal of Animal Science, 2018)
The study was conducted with an aim to investigate the effect of litter density on growth, leg health and litter quality of broiler chickens from d1-42 days. Day-old male broiler chicks (n=400; Cobb 500) were distributed randomly into four litter densities [T1, T2, T3 and T4] treatments, each treatment had 5 replicates with 20 birds per replicate cage in a completely randomized design. Wood shaving was used as litter materials to a thickness of 5 cm, 8 cm, 11 cm and 14 cm on the floor of the pen. Birds were reared on the litter floor open-sided housing condition with ad libitum feed and water throughout the trail period. Data on feed intake (FI), body weight (BW), feed conversion ratio (FCR) and mortality were measured weekly. Litter sample was collected on day 42 to assess the nitrogen content (N2 %), dry matter (DM%) and moisture level (%). Footpad dermatitis (FPD) and hock burn (HB) incidences were measured on day 42 to assess the leg quality of birds. Results demonstrated that litter thickness had no significant (P>0.05) effect on FI, BW, FCR and mortality of broilers from d1-42 days. The N2, DM or moisture levels (%) of litter were also unaffected (P>0.05) between treatment. Leg disorders such as HB and FPD were influenced (P<0.01) by treatment. The incidences of HB and FPD were higher (P<0.01) in T1 and T2 than other treatments. It can be inferred from our current study that, leg health may be deteriorated by using low density wood shaving without affecting growth and litter quality of broiler chickens. Bang. J. Anim. Sci. 2018. 47 (1): 21-27